El zooplancton gelatinoso del Golfo Dulce, Pacífico de Costa Rica, durante la transición de la estación lluviosa a la seca 1997-1998 - Morales-Ramírez, Alvaro (2006)
Gelatinous zooplankton in the Golfo Dulce, Pacific coast of Costa Rica during transition from rainy season to dry season 1997-1998. Gelatinous zooplankton was studied in Golfo Dulce, Pacific coast of Costa Rica during December 1997 and February 1998. Six representative sampling stations were selected and a Niskin bottle was used to collect water and measure temperature, salinity and dissolved oxygen in the water column, every 10 m from the surface to 100 m depth. Zooplankton was collected with a zooplankton net (0.50 m diameter and 500 μm mesh size) with a close-open system in its mouth. Sampling included a hauling in the upper layer, another in or thru the thermocline, and another below the thermocline. Samples were fixed in 4 % formaldehyde; biomass was determinated through the biovolume technique. A picnocline was not found during the study, but strong gradients were detected in the inner station GD02B (oxygen) and the outer station GD11A (temperature and oxygen), with salinity changes in all stations between January and February 1998. We found 41 species of gelatinous zooplankton (33 species of cnidarians, two ctenophores and six thalaceans). Inner and outer stations were clearly different on December but not on February. Abundance and diversity increased from December to February in all stations, while there was a decrease from the month to the inner part of the Gulf for all months. An impact of El Niño was apparent in this community. Rev. Biol. Trop. 54 (Suppl. 1): 201-223. Epub 2006 Sept. 30.